2020
DOI: 10.1111/iji.12474
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatocellular carcinoma risk with polymorphisms in tumour necrosis factor alpha gene in a Chinese Han population

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer‐related death worldwide. Studies have shown that the tumour necrosis factor alpha (TNF‐α) plays an important role in the development of HCC; however, the association between genetic variations of TNF‐α and HCC is not yet fully understood. To evaluate the correlation of TNF‐α polymorphisms with HCC, we randomly selected 327 HCC patients and 432 healthy controls, all these subjects reported Han nationality. Genotyping of four TNF‐α SNPs (rs17997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Our finding showed that the heterozygous genotypes of EGFR rs11977660 T > C, rs3823585 C > G, and rs3735061 G > A appeared to be more susceptible to higher plasma Se concentration, while TNF-α rs1800610 AA genotype played a protective role. In prior studies, TNF-α rs1800610 GA and AA genotypes were associated with a reduced risk in hepatocellular carcinoma [ 50 ], and AA genotype was observed to protect against rheumatoid arthritis [ 51 ], so we supposed that TNF-α rs1800610 AA might be a protective genotype in some pathogeneses. Pb was a toxic metal, but its association with MetS was not consistent [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 98%
“…Our finding showed that the heterozygous genotypes of EGFR rs11977660 T > C, rs3823585 C > G, and rs3735061 G > A appeared to be more susceptible to higher plasma Se concentration, while TNF-α rs1800610 AA genotype played a protective role. In prior studies, TNF-α rs1800610 GA and AA genotypes were associated with a reduced risk in hepatocellular carcinoma [ 50 ], and AA genotype was observed to protect against rheumatoid arthritis [ 51 ], so we supposed that TNF-α rs1800610 AA might be a protective genotype in some pathogeneses. Pb was a toxic metal, but its association with MetS was not consistent [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 98%
“…Tumor necrosis factor (TNF) mediates a variety of cell processes such as inflammation, differentiation, proliferation, and apoptosis. Clinical evidence shows that TNF polymorphisms are associated with susceptibility to cancer, including hepatocellular carcinoma [25], multiple myeloma [26], cervical cancer [27], and colorectal cancer [28]. Tryptophan (Trp) is an essential amino acid that is obtained exclusively from diet and is used for the production of neurotransmitters and neuromodulators.…”
Section: Discussionmentioning
confidence: 99%